Comparative study of design approaches of earth retaining structures - Loh, Martin Vei Tien (2018)
The design of an earth retaining structure is crucial for modern construction works involving underground structures. The computation works involves various uncertainties such as sub-soil profiles, soil properties and lateral stresses. In Singapore, geotechnical engineers utilize the Eurocode 7 (EC7) Design Approach 1 (DA1) combination 1 & 2 to overcome these uncertainties by introducing partial factors into the calculation. However, EC7 has its limitations but it allows designers to use other analytical models to support their claim. To overcome some of these limitations and complement the EC7, designers can choose to use the reliability-based design (RBD) which calculates the probability of failure in the form of a reliability index. This project compared and discussed the results between EC7 design approach and the RBD on two examples of earth retaining structures. The design calculations were carried out on Microsoft Excel. The reliability concept adopted in this report is the first-order reliability method, FORM, with consideration of correlated normal and non-normal random variables. In addition to that, the spreadsheet for RBD was also used to run Monte Carlo simulations in @RISK 7.5. Results show that EC7 Design Approach 1 combination 2 (DA1b) normally is more critical and produces a more conservative design. Other than that, the probabilities of failure resulting from RBD were close to the outcomes of the Monte Carlo simulations. This concludes that RBD can play a useful complementary role to EC7 when a target reliability index or probability of failure is desired.